2019
DOI: 10.1186/s12939-019-1079-y
|View full text |Cite
|
Sign up to set email alerts
|

Geographic differences in maternal and child health care utilization in four Ethiopian regions; a cross-sectional study

Abstract: Background: Maternal and child health (MCH) care utilization often vary with geographic location. We analyzed the geographic distribution and determinants of utilization of four or more antenatal care visits, health facility delivery, child immunization, and care utilization for common childhood illnesses across four Ethiopian regions. Methods: A cross-sectional community-based study was employed with two-staged stratified cluster sampling in 46 districts of Ethiopia. A total of 6321 women (13-49 years) and 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 48 publications
6
34
2
Order By: Relevance
“…The regional and residential variations in ANC contact, however, are not exclusive in Bangladesh as studies from other parts of the world also present similar findings. Studies in Africa suggest regional and residential, urban and rural, variations in accessing ANC [30][31][32][33][34]. Likewise, studies from neighbouring countries of Bangladesh confirm similar results [19,22,[35][36][37][38].…”
Section: Geographic Factorsmentioning
confidence: 52%
“…The regional and residential variations in ANC contact, however, are not exclusive in Bangladesh as studies from other parts of the world also present similar findings. Studies in Africa suggest regional and residential, urban and rural, variations in accessing ANC [30][31][32][33][34]. Likewise, studies from neighbouring countries of Bangladesh confirm similar results [19,22,[35][36][37][38].…”
Section: Geographic Factorsmentioning
confidence: 52%
“…Earlier studies have shown that there are variations in the use of PNC services by regions [12] based on sociocultural differences and some factors affecting PNC service utilization in some facilities [4,11,14].…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Meanwhile, Defar et al [12] have argued that maternal and child health (MCH) care utilisation often varies with geographic location. As such, there is a need for an empirical study examining analysing regional differences in the use of postnatal care services and child morbidity using the recent data from the 2018 NDHS in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an estimated 30% of children under five years of age received oral rehydration salts treatment for diarrhoea from an appropriate health provider in 2016, as compared to 25% in 2011 [4,5]. Studies have reported that lack of geographic and financial access to services, caregivers' limited knowledge of child health danger signs, and poor quality of care at health facilities were some of the reasons for this low utilisation of services [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This activity was not planned to be implemented in 4 districts 6. Community includes AEWs, schoolteachers, WDAs, and HEWs 7. This activity was not planned to be implemented in 8 districts where no budget was allocated for the activity.…”
mentioning
confidence: 99%